Peningkatan Motorik Halus Anak Melalui Mengisi Pola Gambar di Taman Kanak – Kanak Kartika 1-8 Padang - Gusti, Erlinda; Hazizah, Nur (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
The purpose of this study is to improve children's fine motor skills through filling out drawing patterns by drawing lines. Fine motor skills of children in group A TK Kartika 1-8 Padang in the 2019/2020 school year are still low. This research is a class action research, the research was carried out in two cycles and each cycle consisted of 4 stages namely: planning, action, observation and reflection. In each cycle three meetings were held. The method used to collect data is through observation and documentation. Based on the results of the action taken there is an increase in the child's fine motor skills through filling in the image patterns. This can be seen from the results of observing the fine motor abilities of children before the action and after the action. This can be seen in Cycle I with a very good developing average of an average percentage of 31% and an increase in Cycle II with a very good developing average of 86%. This data shows that filling in image patterns can improve children's fine motor skills in Kartika Kindergarten 1-8 Padang